Higher-Order Functions for Parsing - Hutton, Graham (Cambridge University Press, 1992)
In combinator parsing, the text of parsers resembles BNF notation. We present the basic method, and a number of extensions. We address the special problems presented by white-space, and parsers with separate lexical and syntactic phases. In particular, a combining form for handling the offside rule is given. Other extensions to the basic method include an $quot;into$quot; combining form with many useful applications, and a simple means by which combinator parsers can produce more informative error messages.